The Effect of Trichoderma spp. on the Composition of Volatile Secondary Metabolites and Biometric Parameters of Coriander (Coriandrum sativum L.) - E. Gębarowska; M. Pytlarz-Kozicka; J. Nöfer; J. Łyczko; M. Adamski; A. Szumny (Journal of Food Quality)
The aim of this work was to investigate the influence of Trichoderma spp. on volatile secondary metabolites and biometric parameters obtained from coriander (Coriandrum sativum L.). The fruits of coriander treated with liquid suspension spores of T. harzianum strain T22 and of T. asperellum strain B35 increased the yield of essential oil (by ∼36%); however, it was unaffected in its composition. Moreover, Trichoderma spp. influenced the yield and increased the number of seeds of coriander by ∼60%. Inoculation seeds with T. asperelleum strain B35 caused about 2-fold increase in the biomass of the aerial parts of coriander. There was also an increased root colonization by the fungus Trichoderma spp., limiting the number of phytopathogenic fungi from genus Fusarium observed.